ANALISIS MANAJEMEN BANDWIDTH UNTUK PERANCANGAN VOIP (KASUS MTI JTETI FT UGM) - , Ferra Rahadian, Widyawan, S.T., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
VOIP (Voice over IP) is a technology that utilizes the Internet Protocol to provide voice communications electronically and in real-time. VOIP pass voice traffic in packets through the use of IP in the Internet network. The main problem faced by the VOIP is the level of delay and packet loss. Queue FIFO method (first in, first out) can not set the package with a certain priority, because all packets are considered equal. If the packet queue VOIP comes together with the data packet delay there will be high enough. Methods HTB (Hierarchy Token Bucket) is one method that is included in the queue queuing Classfull Discipline. Classfull queue discipline is a method of queuing with multiple classes (multiple classes), so the possible different configurations for each class. The purpose of this study is to an analyse of the effect of the implementation of bandwidth management using the HTB (Hierarchy Token Bucket) to the QoS of VoIP service on a computer network MTI Department of Electrical Engineering and Information Technology Faculty of Engineering UGM. Bandwidth management mechanism used is a mechanism of sharing the bandwidth and priority service. In general the results of this research shows that the implementation of bandwidth management using HTB with bandwidth sharing mechanism, obtained the value of QoS in VoIP service and consistently better than the service priority mechanisms. However, the jitter values obtained by the method of HTB is greater than the FIFO method.